Realization of Tunable Photonic Spin Hall Effect by Tailoring the Pancharatnam-Berry Phase - Ling, Xiaohui (Nature Publishing Group, 2014)
Recent developments in the field of photonic spin Hall effect (SHE) offer new opportunities for advantageous measurement of the optical parameters (refractive index, thickness, etc.) of nanostructures and enable spin-based photonics applications in the future. However, it remains a challenge to develop a tunable photonic SHE with any desired spin-dependent splitting for generation and manipulation of spin-polarized photons. Here, we demonstrate experimentally a scheme to realize the photonic SHE tunably by tailoring the space-variant Pancharatnam-Berry phase (PBP). It is shown that light beams whose polarization with a tunable spatial inhomogeneity can contribute to steering the space-variant PBP which creates a spin-dependent geometric phase gradient, thereby possibly realizing a tunable photonic SHE with any desired spin-dependent splitting. Our scheme provides a convenient method to manipulate the spin photon. The results can be extrapolated to other physical system with similar topological origins.